Transformative teacher education in economics: reflection on service learning in Ibadan (2023)
This study focused on the relevance of service learning to transformative teacher education. The researchers used a qualitative approach and a case study design, involving 300 level Economics Education students at the Faculty of Education, University of Ibadan in Nigeria during the 2017/2018 academic session. Data was collected through interviews and students' journals, which were analyzed thematically. The findings indicated that service learning is an effective means of improving teacher education, as it enhances students' attitudes towards teaching, promotes transformative learning, and improves the employability skills of pre-service teachers. The study also revealed that service learning fosters a positive attitude from school management towards student-teachers and helps eliminate boredom in the teaching and learning process. As a recommendation, the study proposes that the teacher education curriculum should be revised to include service learning as a way to promote meaningful learning and professional development among future teachers in the 21st century among others.